Simple Estimate of the Impact of M2 and Strehl Ratio on the Effective Focusable Spot Size - Samuel Arba-Mosquera; Pascal Naubereit; Simas Sobutas (Optics, 2024)
A simple method (first-order approximation) to determine the impact of M2 and the Strehl Ratio on the effective focusable spot size avoiding complex propagations of the beam wavefront is proposed. The model is based upon previous models and the definition of M2 and the Strehl Ratio in a simple manner. This work provides qualitative and quantitative estimates for the interplay of M2 and the Strehl Ratio on the effectively focusable spot size.